Cannabis Use, Medication Management and Adherence among Persons Living with HIV - Vidot, Denise C. (AIDS Behav, 2017)
Cannabis is used to relieve nausea, trigger weight gain, and reduce pain among adults living with HIV; however, the relationship between its use and medication adherence and management is unclear. Participants (N = 107) were from an ongoing cohort study of community-dwelling HIV+ adults, stratified by cannabis (CB) use: HIV+/CB+ (n = 41) and HIV+/CB− (n = 66). CB+ participants either tested positive in a urine toxicology screen for THC or had a self-reported history of regular and recent use. HIV-status was provided by physician results and/or biomarker assessment. Adherence was measured via the Morisky scale and medication management was assessed via the Medication Management Test-Revised. After adjusting for gender, we found no association between cannabis use group and adherence nor medication management. The amount of cannabis used was also not associated with measures of adherence and management. Preliminary findings suggest that cannabis use may not adversely influence medication adherence/management among adults living with HIV.